2017
DOI: 10.1016/j.jtcme.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of bartogenic acid containing fraction of fruits of Barringtonia racemosa Roxb. in acute and chronic animal models of inflammation

Abstract: The fruits of Barringtonia racemosa are traditionally used in Indian medicine for the treatment of pain and inflammatory conditions. In this study, a fraction of ethyl acetate extract of fruits of B. racemosa (BREAF) was investigated for anti-inflammatory activity in experimental models of acute and chronic inflammation. Activity against acute inflammation was evaluated in inflammogens induced rat paw edema models. Whereas, effect in chronic inflammation was evaluated in cotton pellet granuloma and oxazolone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 54 publications
1
37
0
2
Order By: Relevance
“…The formation of granuloma tissues were enhanced by pro-inflammatory mediators, reactive oxygen species and lysosomal enzymes activities [16]. This study revealed that BA and BAA exhibited potent antiinflammatory activity [5]. This implied that the compounds can enhance the upregulation of anti-inflammatory cytokines or downregulation of pro-inflammatory mediators such as: nitric oxide, myeloperioxidase and some interleukins [5].…”
Section: Iron Chelationmentioning
confidence: 83%
See 2 more Smart Citations
“…The formation of granuloma tissues were enhanced by pro-inflammatory mediators, reactive oxygen species and lysosomal enzymes activities [16]. This study revealed that BA and BAA exhibited potent antiinflammatory activity [5]. This implied that the compounds can enhance the upregulation of anti-inflammatory cytokines or downregulation of pro-inflammatory mediators such as: nitric oxide, myeloperioxidase and some interleukins [5].…”
Section: Iron Chelationmentioning
confidence: 83%
“…This study revealed that BA and BAA exhibited potent antiinflammatory activity [5]. This implied that the compounds can enhance the upregulation of anti-inflammatory cytokines or downregulation of pro-inflammatory mediators such as: nitric oxide, myeloperioxidase and some interleukins [5]. Previously, pentacyclic triterpenes like bartogenic acid have been reported to possess antiinflammatory activity.…”
Section: Iron Chelationmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the hyperalgesia (exacerbated sensitivity to thermal and mechanical stimuli) provoked by carrageenan, makes it appropriate for the study inflammatory pain [29]. Two phases of inflammation are induced by λ-carrageenan: the first -that occurs within an hour of injection -that is associated with histamine, serotonin and bradykinin liberation, and the secondfrom 1-3 or more hours -characterized by prostaglandin production [30].…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan injection into the sub plantar surface of rat paw is characterized by biphasic response with the involvement of different inflammatory mediators. The early phase observed (1-2 h) is mediated by histamine and serotonin and delayed phase (3-4 h) is mediated with the release of prostaglandins 26 . Our results indicate that the administration of SC-EA extracts inhibited the edema during acute phase of inflammation probably by inhibiting the chemical mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%